Effects of active video games on mental health among college students: a systematic review - Zhao, Yue; Soh, Kim Geok; Abu Saad, Hazizi; Rong, Wenchao; Liu, Cong; Wang, Xinzhi (BioMed Central, 2024)
Background: Mental health significantly impacts college students’ academic performance and overall happiness. Active video games (AVGs) have gained popularity among college students due to their ample entertainment, and there is growing interest in utilizing them to address mental health issues. However, there has not been a com- prehensive summary and systematic review of research on the effects of AVGs on college students’ mental health. Methods: As of October 18th, 2024, searches were conducted in six internationally renowned databases (PubMed, SCOPUS, Web of Science, CINAHL Plus, EBSCOhost, Cochrane Library). Inclusion and exclusion criteria were developed based on the PICOS principles. A systematic review was conducted following the PRISMA guidelines, and compliant studies using randomised controlled trial design (RCT) were included. The methodological quality of the included studies was evaluated using the PEDro scale. Results: A total of 3471 articles were retrieved, of which 17 met the criteria inclusion. The PEDro scores of the 17 studies ranged from four to nine. The results indicate that AVGs can effectively improve college students’ poor mental health, such as stress, anxiety, and depression, as well as increase their happiness and psychological satisfaction. More- over, AVGs have been shown to increase motivation for exercise, improve college students’ attitudes toward other forms of exercise, and promote sustained physical activity. Additionally, AVGs have demonstrated efficacy in improv- ing sleep quality. Conclusion: Overall, AVGs can serve as an effective intervention to reduce dysphoria and promote positive psycho- logical states among college students, thus improving mental health. Using the theory-based design of AVGs will further increase the effect. However, the effects of AVGs vary depending on their type and initial design purpose. Therefore, when using AVGs to improve college students’ mental health, it is necessary to carefully consider the stu- dents’ original state, select AVGs with rich game content that can provide at least moderate-intensity physical activity, and adopt the correct intervention strategy to achieve good results. AVG can potentially become a valuable tool for improving college students’ mental health.